Unintentional Bias dan Opini Audit Going Concern - Roza, Husna; Suhernita, Suhernita; Yohana, Denny (Unand Press, 2019)
This study examines the relationship between unintentional biasand going concern audit opinion. This study involved accounting students who acted as professional auditors. This study adopted the experimental material used in(Andres Guiral, Rodgers, Ruiz, & Gonzalo-Angulo, 2015) . This study found evidence that the auditor's sensitivity to litigation risk and perceptions of the whistleblowing function were positively associated with going concern audit opinion. Furhter, this study found no relationship between self-fulfilling prophecybias and going concern opinion